Vanadium-based high-entropy alloy catalyst as well as preparation method and application thereof

By introducing V elements into high-entropy alloy catalysts and adjusting the electronic structure, the vanadium-based high-entropy alloy catalyst ZnCoNiFeV@NC was designed, which solved the problem of slow kinetics and large potential of the oxygen evolution catalyst in the electrolytic water reaction, and achieved efficient dielectric transmission and stable catalytic performance.

CN119592993APending Publication Date: 2025-03-11NORTH CHINA UNIV OF WATER RESOURCES & ELECTRIC POWER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411643211.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing oxygen evolution catalysts in electrolytic water reactions have problems such as slow reaction kinetics and large electric potential, especially the oxygen evolution reaction of the four electrons seriously restricts the efficiency of electrolytic water.

Method used

A vanadium-based high-entropy alloy catalyst ZnCoNiFeV@NC is designed to adjust the electronic structure by introducing V elements into the high-entropy alloy, improving the medium transmission function, thereby improving the catalytic performance.

Benefits of technology

The catalyst has an overpotential value of only 284mV at 10mA cm-2 and a stable output time of 45h, which is significantly better than the same type of catalyst, and has a high specific surface area and abundant surfactant sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592993A_ABST
    Figure CN119592993A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oxygen evolution catalysts, in particular to a vanadium-based high-entropy alloy catalyst and a preparation method and application thereof. The vanadium-based high-entropy alloy catalyst is composed of a high-entropy alloy component and a carbon component coating the surface of the high-entropy alloy component, the high-entropy alloy component is Fe, Co, Ni, Zn and V, and the microstructure of the high-entropy alloy component is of a spherical flower-shaped structure formed by polymerizing nanosheet layers; the preparation method of the vanadium-based high-entropy alloy catalyst sequentially comprises the following steps: preparing a metal salt mixed solution, an organic mixed solution, a metal organic framework precursor and the vanadium-based high-entropy alloy catalyst; the vanadium-based high-entropy alloy catalyst not only has high specific surface area and high content of surface functional groups, but also effectively reduces the reaction energy barrier of oxygen evolution reaction by introducing a V element into the catalyst to adjust the electronic structure of the high-entropy alloy, so that the overpotential of the catalyst is only 284mV at 10mA cm <-2 >, and the stable output time of the catalyst which does not present a decline trend is 45h; the catalyst is far better than the same catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oxygen evolution catalysts, and in particular to a vanadium-based high entropy alloy catalyst and a preparation method and application thereof. Background Art

[0002] In order to solve the problem of energy shortage, clean energy technologies such as water electrolysis to produce hydrogen have been favored by researchers. However, the cathode hydrogen evolution reaction and the anode oxygen evolution reaction of water electrolysis face problems such as slow over-reaction kinetics and high potential. In particular, the four-electron oxygen evolution reaction seriously restricts the efficiency of water electrolysis.

[0003] In order to improve the efficiency of water electrolysis, oxygen evolution catalysts can be used. Among the many oxygen evolution reaction catalysts, precious metal catalysts such as IrO2 are expensive and difficult to use on a large scale. Traditional transition metal catalysts face problems such as insufficient activity.

[0004] The emerging high-entropy alloy catalysts have unique high-entropy effect, lattice distortion effect, hysteresis diffusion effect, and cocktail effect, which can maximize the synergistic mechanism of multiple active ingredients and thus greatly enhance the catalytic effect.

[0005] The high entropy alloy catalyst includes non-precious metal alloys and precious metal alloys. Among them, the non-precious metal alloy catalysts are concentrated on metals such as Cr, Mn, Fe, Co, and Ni. These metals have similar electronic structures, and it is difficult to optimize the electronic structure of the catalyst to the greatest extent. Precious metal catalysts further improve the activity and stability of the catalyst by introducing active centers such as Ru and Pt, but they also face problems such as high cost.

[0006] Therefore, the inventors are committed to modifying the existing high entropy alloy catalysts by designing new nanostructures to enable them to carry more active sites, thereby improving the reaction process's ability to promote medium transmission and improving catalytic performance. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a vanadium-based high entropy alloy catalyst, namely, ZnCoNiFeV@NC catalyst, by introducing V into the high entropy alloy to adjust the electronic structure of the high entropy alloy, thereby obtaining an oxygen evolution catalyst with higher medium transport function.

[0008] The present invention provides a vanadium-based high entropy alloy catalyst, which is composed of a high entropy alloy component and a carbon component coated on the surface of the high entropy alloy component, and the mass ratio of the high entropy alloy component to the carbon component is 1:(3.5-5);

[0009] The high entropy alloy components are face-centered cubic structures, and are composed of uniformly distributed transition metals Fe, Co, Ni, Zn, and modified metal V, and the molar ratio of Fe, Co, Ni, Zn, and V is 2:2:2:2:(1-3);

[0010] Note: The addition of V can effectively reduce the reaction energy barrier of oxygen evolution reaction and accelerate the reaction rate;

[0011] The microstructure of the vanadium-based high-entropy alloy catalyst is a spherical flower-like structure with a diameter of 200 to 600 nm, which is composed of nanosheets with a thickness of 10 to 20 nm. Its specific surface area is 100 to 300 m 2 / g, pore size is 1.3~1.5nm, pore volume is 0.1~0.2cm 3 / g; at 10mA cm -2 The potential at the bottom is 284 mV.

[0012] As another aspect of the present invention, a method for preparing the above-mentioned vanadium-based high entropy alloy catalyst is also provided, comprising the following steps:

[0013] S1, preparing a metal salt mixture;

[0014] Add five groups of metal salts as reactants to deionized water in sequence, and perform ultrasonic stirring after each addition of a group of metal salts, to finally obtain a metal salt mixture; the five groups of metal salts are ZnCl2, CoCl2, NiCl2, FeCl3 and VCl4;

[0015] Let n be the multiplication coefficient and n∈R + , then in the metal salt mixture, the content of deionized water is 10n mL, the content of ZnCl2 is 0.2n mmol, the content of CoCl2 is 0.2n mmol, the content of NiCl2 is 0.2n mmol, the content of FeCl3 is 0.2n mmol, and the content of VCl4 is [0.1,0.3]n mmol;

[0016] S2, preparing an organic mixed solution;

[0017] Add three groups of reactants to deionized water in sequence, and perform ultrasonic stirring after adding one group of reactants each time, and finally obtain an organic mixed solution; the three groups of reactants are NaOH, 2-aminoterephthalic acid and 4,4′-bipyridine;

[0018] Let n be the multiplication coefficient and n∈R + , then in the organic mixed solution, the content of deionized water is 20n mL, the content of NaOH is 4n mmol, the content of 2-aminoterephthalic acid is 2n mmol, and the content of 4,4′-bipyridine is [1,3]nmmol;

[0019] Description: 2-aminoterephthalic acid reacts with NaOH to protonate 2-aminoterephthalic acid;

[0020] S3, preparing metal organic framework precursors;

[0021] The metal salt mixture is added to the organic mixture, and the mixture is subjected to ultrasonic stirring to obtain a precursor mixture, which is then filtered, and then the filtrate is washed with deionized water and anhydrous ethanol respectively until the washing liquid is clear, and finally the washing is dried to obtain a metal organic framework precursor;

[0022] In the precursor mixture, the ratio of the metal salt mixture to the organic mixture is as follows: the ratio of the mole number of 2-aminoterephthalic acid to the total mole number of the five groups of metal salts is 1:1;

[0023] S4, preparing a vanadium-based high entropy alloy catalyst;

[0024] The metal organic framework precursor prepared in S3 is subjected to heat treatment and then furnace annealed to a specific temperature range to obtain a vanadium-based high entropy alloy catalyst, namely, ZnCoNiFeV@NC catalyst;

[0025] Furthermore, the parameters of ultrasonic stirring in S1 and S2 are: ultrasonic frequency: 20kHz; ultrasonic amplitude: 15μm; stirring rate: 1000r / min, stirring time: 3-5min;

[0026] The parameters of ultrasonic stirring in S3 are: ultrasonic frequency: 20 kHz; ultrasonic amplitude: 15 μm; stirring rate: 1000 r / min, and stirring time: 0.5 to 2 min.

[0027] Furthermore, the parameters of the laundry drying process in S2 are: drying temperature: 60-70° C., and drying time: 6-15 hours.

[0028] Furthermore, the parameters of the heating treatment in S4 are: in an inert atmosphere, the temperature is increased from room temperature to 800-1000° C. at a heating rate of 5° C. / min, and kept at this temperature for 2-4 hours.

[0029] Furthermore, the specific temperature range in S4 is 25-50°C.

[0030] Note: The upper limit of the temperature range of 50°C here means that when the heated metal organic framework precursor is cooled to 50°C or below with the furnace, its crystal structure is fixed; 25°C is the external ambient temperature, and the lowest temperature when the furnace is cooled is equal to the external temperature; in summary, when the metal organic framework precursor is cooled to any temperature in the range of 25-50°C with the furnace, removing the finished product from the furnace will not affect its physical properties.

[0031] As another aspect of the present invention, an application of the above-mentioned vanadium-based high entropy alloy catalyst is also provided, and the designed vanadium-based high entropy alloy catalyst is used as an oxygen evolution catalyst for water electrolysis reaction.

[0032] When vanadium-based high entropy alloy catalysts are used in catalytic water electrolysis: in 1M KOH electrolyte, it is 10mAcm -2 The potential under overpotential is 284 mV, the Tafel slope is 51.9 mV·dec-1, and the TOF value is 0.8 s at an overpotential of 100 mV. -1 The stable output time without showing a downward trend is 45h.

[0033] Compared with the existing oxygen evolution catalyst, the beneficial effects of the present invention are:

[0034] (1) The ZnCoNiFeV@NC catalyst designed by the present invention introduces the V element into the catalyst to adjust the electronic structure of the high entropy alloy, thereby effectively reducing the reaction energy barrier of the oxygen evolution reaction. -2 The lower overpotential is only 284mV, and the stable output time without showing a downward trend is 45h, which is much better than the same type of oxygen evolution catalyst.

[0035] (2) The ZnCoNiFeV@NC catalyst designed by the present invention has a microscopic morphology of a spherical nanoflower structure composed of a plurality of nanosheet layers, and thus has an extremely high specific surface area and more abundant surface active sites, that is, has a higher medium transmission function. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The scanning electron microscope photographs of the ZnCoNiFeV@NC catalyst and the control group sample in Example 2;

[0037] Figure 2 This is the element mapping photo corresponding to the mapping of the ZnCoNiFeV@NC catalyst in Example 2;

[0038] Figure 3 X-ray diffraction patterns of the ZnCoNiFeV@NC catalyst and the control group sample in Example 2;

[0039] Figure 4 Polarization curves of ZnCoNiFeV@NC catalyst and control group samples in 1M KOH in Example 2;

[0040] Figure 5 This is a graph showing the stability test results of the ZnCoNiFeV@NC catalyst in Example 2.

[0041] Figure 6Scanning electron microscope photos of ZnCoNiFeV@NC-850 catalyst and ZnCoNiFeV@NC-1000 catalyst at different temperatures in Examples 3 and 4;

[0042] Figure 7 Polarization curves of ZnCoNiFeV@NC-850 catalyst and ZnCoNiFeV@NC-1000 catalyst in Examples 3 and 4 at different temperatures in 1 M KOH. DETAILED DESCRIPTION

[0043] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0044] Example 1: This example describes a vanadium-based high entropy alloy catalyst.

[0045] The vanadium-based high entropy alloy catalyst prepared in this embodiment is composed of a high entropy alloy component and a carbon component coated on the surface of the high entropy alloy component, and the mass ratio of the high entropy alloy component to the carbon component is 1:(3.5-5);

[0046] The high entropy alloy components are face-centered cubic structures, and are composed of uniformly distributed transition metals Fe, Co, Ni, Zn, and modified metal V, and the molar ratio of Fe, Co, Ni, Zn, and V is 2:2:2:2:(1-3);

[0047] The microstructure of the vanadium-based high-entropy alloy catalyst is a spherical flower-like structure with a diameter of 200 to 600 nm, which is composed of nanosheets with a thickness of 10 to 20 nm. Its specific surface area is 100 to 300 m 2 / g, pore size is 1.3~1.5nm, pore volume is 0.1~0.2cm 3 / g; at 10mA cm -2 The potential at the bottom is 284 mV.

[0048] Example 2: This example describes a method for preparing the vanadium-based high entropy alloy catalyst in Example 1.

[0049] S1, preparing a metal salt mixture;

[0050] Five groups of metal salts as reactants are sequentially added to deionized water, and ultrasonic stirring is performed after each group of metal salts is added, and finally a metal salt mixture is obtained; the five groups of metal salts are ZnCl2, CoCl2, NiCl2, FeCl3 and VCl4; the parameters of ultrasonic stirring are: ultrasonic frequency: 20kHz; ultrasonic amplitude: 15μm; stirring rate: 1000r / min, stirring time: 3min;

[0051] In the metal salt mixture, the content of deionized water is 10 mL, the content of ZnCl2 is 0.2 mmol, the content of CoCl2 is 0.2 mmol, the content of NiCl2 is 0.2 mmol, the content of FeCl3 is 0.2 mmol, and the content of VCl4 is 0.2 mmol;

[0052] S2, preparing an organic mixed solution;

[0053] Three groups of reactants are added to deionized water in sequence, and ultrasonic stirring is performed after each group of reactants is added to finally obtain an organic mixed solution; the three groups of reactants are NaOH, 2-aminoterephthalic acid and 4,4′-bipyridine; the parameters of ultrasonic stirring are: ultrasonic frequency: 20kHz; ultrasonic amplitude: 15μm; stirring rate: 1000r / min, stirring time: 3min

[0054] In the organic mixed solution, the content of deionized water is 20 mL, the content of NaOH is 4 mmol, the content of 2-aminoterephthalic acid is 2 mmol, and the content of 4,4′-bipyridine is 2 mmol;

[0055] S3, preparing metal organic framework precursors;

[0056] The metal salt mixture is added to the organic mixture, and the mixture is subjected to ultrasonic stirring to obtain a precursor mixture, and then filtered. The filtrate is then washed twice with deionized water and anhydrous ethanol, respectively, and finally the washed product is dried at 60°C for 6 hours to obtain a metal organic framework precursor. The parameters of the ultrasonic stirring are: ultrasonic frequency: 20kHz; ultrasonic amplitude: 15μm; stirring rate: 1000r / min, stirring time: 0.5min;

[0057] In the precursor mixture, the ratio of the metal salt mixture to the organic mixture is as follows: the ratio of the mole number of 2-aminoterephthalic acid to the total mole number of the five groups of metal salts is 1:1;

[0058] S4, preparing a vanadium-based high entropy alloy catalyst;

[0059] In an inert atmosphere, the metal organic framework precursor prepared in S3 was heated from room temperature to 800°C at a heating rate of 5°C / min, kept at this temperature for 2 h, and then furnace annealed to 25°C to obtain the ZnCoNiFeV@NC catalyst.

[0060] Example 3: The contents of this example are based on Example 2 and are intended to illustrate the preparation method under another parameter. Except for the following contents, the rest are the same as those in Example 2.

[0061] S4, preparing a vanadium-based high entropy alloy catalyst;

[0062] In an inert atmosphere, the metal organic framework precursor prepared in S3 was heated from room temperature to 850°C at a heating rate of 5°C / min, kept at this temperature for 2 h, and furnace annealed to 25°C to obtain the ZnCoNiFeV@NC-850 catalyst.

[0063] Figure 6 Scanning electron microscope photographs of the ZnCoNiFeV@NC-850 catalyst and the ZnCoNiFeV@NC-1000 catalyst prepared in Example 3 at different temperatures show that the catalyst has a spherical flower-like structure composed of sheets.

[0064] Figure 7 Polarization curves of the ZnCoNiFeV@NC-850 catalyst and the ZnCoNiFeV@NC-1000 catalyst prepared in Example 3 of the present invention in 1 M KOH at different temperatures show that the catalysts still have good oxygen evolution reaction activity.

[0065] Example 4: The contents of this example are based on Example 2 and are intended to illustrate the preparation method under another parameter. Except for the following contents, the rest are the same as those in Example 2.

[0066] S4, preparing a vanadium-based high entropy alloy catalyst;

[0067] In an inert atmosphere, the metal organic framework precursor prepared in S3 was heated from room temperature to 1000°C at a heating rate of 5°C / min, kept at this temperature for 2 h, and furnace annealed to 25°C to obtain the ZnCoNiFeV@NC-1000 catalyst.

[0068] Figure 6 Scanning electron microscope photographs of the ZnCoNiFeV@NC-850 catalyst and the ZnCoNiFeV@NC-800 catalyst prepared in Example 3 at different temperatures show that the catalyst has a spherical flower-like structure composed of sheets.

[0069] Figure 7 Polarization curves of the ZnCoNiFeV@NC-850 catalyst and the ZnCoNiFeV@NC-800 catalyst prepared in Example 3 of the present invention in 1 M KOH at different temperatures show that the catalysts still have good oxygen evolution reaction activity.

[0070] Example 5: The contents of this example are based on Example 2 and are intended to illustrate the preparation method under another parameter. Except for the following contents, the rest are the same as those in Example 2.

[0071] S4, preparing a vanadium-based high entropy alloy catalyst;

[0072] In an inert atmosphere, the metal organic framework precursor prepared in S3 was heated from room temperature to 900°C at a heating rate of 5°C / min, kept at this temperature for 2 h, and then furnace annealed to 25°C to obtain the ZnCoNiFeV@NC catalyst.

[0073] Example 6: The contents of this example are based on Example 2 and are intended to illustrate the preparation method under another parameter. Except for the following contents, the rest are the same as those in Example 2.

[0074] In the metal salt mixture, the content of deionized water is 10 mL, the content of ZnCl2 is 0.2 mmol, the content of CoCl2 is 0.2 mmol, the content of NiCl2 is 0.2 mmol, the content of FeCl3 is 0.2 mmol, and the content of VCl4 is 0.1 mmol;

[0075] In the organic mixed solution, the content of deionized water is 20 mL, the content of NaOH is 4 mmol, the content of 2-aminoterephthalic acid is 2 mmol, and the content of 4,4′-bipyridine is 1 mmol;

[0076] The metal salt mixture was added to the organic mixture, and ultrasonic stirring was performed for 2 minutes to obtain a precursor mixture, which was then filtered, and then the filtrate was washed with deionized water and anhydrous ethanol for 3 times, and finally the washed product was dried at 70°C for 15 hours to obtain a metal organic framework precursor.

[0077] In an inert atmosphere, the MOF precursor prepared in S3 was heated from room temperature to 900°C at a heating rate of 5°C / min and kept at this temperature for 4 h.

[0078] Example 7: The contents of this example are based on Example 2 and are intended to illustrate the preparation method under another parameter. Except for the following contents, the rest are the same as those in Example 2.

[0079] In the metal salt mixture, the content of deionized water is 10 mL, the content of ZnCl2 is 0.2 mmol, the content of CoCl2 is 0.2 mmol, the content of NiCl2 is 0.2 mmol, the content of FeCl3 is 0.2 mmol, and the content of VCl4 is 0.3 mmol;

[0080] In the organic mixed solution, the content of deionized water is 20 mL, the content of NaOH is 4 mmol, the content of 2-aminoterephthalic acid is 2 mmol, and the content of 4,4′-bipyridine is 3 mmol;

[0081] The metal salt mixture was added to the organic mixture, and ultrasonic stirring was performed for 2 minutes to obtain a precursor mixture, which was then filtered, and then the filtrate was washed with deionized water and anhydrous ethanol for 3 times, and finally the washed product was dried at 70°C for 15 hours to obtain a metal organic framework precursor.

[0082] In an inert atmosphere, the MOF precursor prepared in S3 was heated from room temperature to 900°C at a heating rate of 5°C / min and kept at this temperature for 4 h.

[0083] Experimental Example: The description of this experimental example is based on the scheme described in Example 2, and is intended to illustrate the practical application effect of the present invention.

[0084] 1. Experimental design: In order to compare the performance differences between the ZnCoNiFeV@NC catalyst prepared by the present invention and other catalysts, the following experimental groups were designed:

[0085] Blank group: Example 2;

[0086] Control group 1: The difference from Example 2 is that only 0.5 mmol of Zn and 0.5 mmol of Co were added as metal components of the catalyst;

[0087] Control group 2: The difference from Example 2 is that only 0.5 mmol of Zn, 0.5 mmol of Co and 0.33 mmol of Ni are added as metal components of the catalyst;

[0088] Control group 3: The difference from Example 2 is that only 0.25 mmol of Zn, 0.25 mmol of Co, 0.25 mmol of Ni and 0.25 mmol of Fe are added as metal components of the catalyst;

[0089] Figure 1 The scanning electron microscope images of Example 2 and the control group show that the prepared catalysts all show a flower-like morphology.

[0090] Figure 2 This is the element mapping diagram of the ZnCoNiFeV@NC catalyst in Example 2. It can be seen that various elements are evenly distributed in the catalyst.

[0091] Figure 3 This is the X-ray diffraction pattern of the ZnCoNiFeV@NC catalyst in Example 2. It can be seen that the catalyst is a metal alloy with a face-centered cubic structure and is very pure.

[0092] Figure 4 The polarization curves of the ZnCoNiFeV@NC catalyst and the control sample in Example 3 in 1 M KOH show that the activity of the ZnCoNiFeV@NC catalyst is significantly better than that of the control sample at 10 mA cm-2 The lower overpotential is only 284 mV, which is much smaller than 326 mV of ZnCoNiFe@NC, 485 mV of ZnCoNi@NC, and 393 mV of ZnCo@NC.

[0093] 2. Experimental design: In order to illustrate the electrochemical performance of the ZnCoNiFeV@NC catalyst prepared in the present invention, the following experiments were designed and the test data were obtained.

[0094] Experimental conditions: 5 mg of catalyst was dispersed in 960 μL of isopropanol and 40 μL of Nafion was added. Then 16 μL of catalyst was pipetted onto a 5 mm diameter glassy carbon electrode. After drying, the polarization curve was tested in 1 M KOH. The reference electrode was an Ag / AgCl electrode, the counter electrode was a graphite rod, and the scan rate was 10 mV s -1 .

[0095] Test data: In 1M KOH electrolyte, at 10mA cm -2 The potential under overpotential is 284 mV, the Tafel slope is 51.9 mV·dec-1, and the TOF value is 0.8 s at an overpotential of 100 mV. -1 .

[0096] And from Figure 5 The stability test results show that the catalyst has a stable output time of 45 hours without showing a downward trend, that is, the potential does not change significantly, and has excellent catalytic stability.

Claims

1. A vanadium-based high entropy alloy catalyst, characterized in that: The vanadium-based high entropy alloy catalyst is composed of a high entropy alloy component and a carbon component coated on the surface of the high entropy alloy component, and the mass ratio of the high entropy alloy component to the carbon component is 1:(3.5-5); The high entropy alloy component is a face-centered cubic structure, and is composed of uniformly distributed transition metals Fe, Co, Ni, Zn, and modified metal V, and the molar ratio of the Fe, Co, Ni, Zn and V is 2:2:2:2:(1-3); The microstructure of the vanadium-based high entropy alloy catalyst is a spherical flower-like structure with a diameter of 200 to 600 nm formed by polymerization of nanosheets with a thickness of 10 to 20 nm, and a specific surface area of ​​100 to 300 m 2 / g, pore size is 1.3~1.5nm, pore volume is 0.1~0.2cm 3 / g.

2. The method for preparing a vanadium-based high entropy alloy catalyst according to claim 1, characterized in that: The following steps are involved: S1, preparing a metal salt mixture; Add five groups of metal salts as reactants to deionized water in sequence, and perform ultrasonic stirring after each addition of a group of metal salts, to finally obtain a metal salt mixture; the five groups of metal salts are ZnCl2, CoCl2, NiCl2, FeCl3 and VCl4; Let n be the multiplication coefficient and n∈R + , then in the metal salt mixture, the content of deionized water is 10n mL, the content of ZnCl2 is 0.2n mmol, the content of CoCl2 is 0.2n mmol, the content of NiCl2 is 0.2n mmol, the content of FeCl3 is 0.2nmmol, and the content of VCl4 is [0.1,0.3]n mmol; S2, preparing an organic mixed solution; Add three groups of reactants to deionized water in sequence, and perform ultrasonic stirring after adding one group of reactants each time, to finally obtain an organic mixed solution; the three groups of reactants are NaOH, 2-aminoterephthalic acid and 4,4′-bipyridine; Let n be the multiplication coefficient and n∈R + , then in the organic mixed solution, the content of deionized water is 20n mL, the content of NaOH is 4nmmol, the content of 2-aminoterephthalic acid is 2n mmol, and the content of 4,4′-bipyridine is [1,3]n mmol; S3, preparing metal organic framework precursor; The metal salt mixed solution is added to the organic mixed solution, and the mixed solution is subjected to ultrasonic stirring to obtain a precursor mixed solution, which is then filtered, and then the filtered solution is washed with deionized water and anhydrous ethanol respectively until the washing solution is clear, and finally the washed solution is dried to obtain a metal organic framework precursor; In the precursor mixture, the ratio of the metal salt mixture to the organic mixture is: the ratio of the mole number of 2-aminoterephthalic acid to the total mole number of the five groups of metal salts is 1:1; S4, preparing a vanadium-based high entropy alloy catalyst; The metal organic framework precursor prepared in S3 is subjected to heat treatment and then furnace annealed to a specific temperature range to obtain a vanadium-based high entropy alloy catalyst, namely, ZnCoNiFeV@NC catalyst.

3. The method for preparing a vanadium-based high entropy alloy catalyst according to claim 2, characterized in that: The parameters of ultrasonic stirring in S1 and S2 are: ultrasonic frequency: 20kHz; ultrasonic amplitude: 15μm; stirring rate: 1000r / min, stirring time: 3-5min; The parameters of the ultrasonic stirring in S3 are: ultrasonic frequency: 20 kHz; ultrasonic amplitude: 15 μm; stirring rate: 1000 r / min, and stirring time: 0.5 to 2 min.

4. The method for preparing a vanadium-based high entropy alloy catalyst according to claim 2, characterized in that: The parameters of the laundry drying process in S2 are: drying temperature: 60-70° C., and drying time: 6-15 hours.

5. The method for preparing a vanadium-based high entropy alloy catalyst according to claim 2, characterized in that: The parameters of the heating treatment in S4 are: in an inert atmosphere, the temperature is increased from room temperature to 800-1000° C. at a heating rate of 5° C. / min, and the temperature is kept for 2-4 hours.

6. The method for preparing a vanadium-based high entropy alloy catalyst according to claim 2, characterized in that: The specific temperature range in S4 is 25-50°C.

7. The use of a vanadium-based high entropy alloy catalyst as claimed in claim 1, characterized in that: The vanadium-based high entropy alloy catalyst is an oxygen evolution catalyst for water electrolysis reaction.

8. The use of a vanadium-based high entropy alloy catalyst as claimed in claim 7, characterized in that: When the vanadium-based high entropy alloy catalyst is used to catalyze the electrolysis of water: in 1M KOH electrolyte, at 10 mA cm -2 The potential under overpotential is 284 mV, the Tafel slope is 51.9 mV·dec-1, and the TOF value is 0.8 s at an overpotential of 100 mV. -1 The stable output time without showing a downward trend is 45h.